Effects of corn processing and wet corn gluten feed on newly received and growing cattle - A.V. Siverson; Brandon E. Oleen; Evan C. Titgemeyer; Sean P. Montgomery; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2013)
Newly arrived feedlot cattle present numerous challenges and are often considered to be the most difficult type of fed cattle to handle. Receiving cattle typically are highly stressed and have had feed withheld for a significant amount of time. Formulating rations that are cost-effective and nutrient-dense is essential to accommodating lowered intake. The objective of this experiment was to evaluate effects of corn processing (whole shelled or dry-rolled), wet corn gluten feed (WCGF) inclusion, and their interaction on cattle performance.
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-162-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1083; Cattle; Corn Processing; Wet corn gluten; Cattle performance; Dry rolled corn